Sol‐gel based copper metallic layer as external anode for microtubular solid oxide fuel cell. (14th May 2022) - Shabri, Hazrul Adzfar; Rudin, Siti Norlaila Faeizah Mohd; Othman, Mohd Hafiz Dzarfan; Jamil, Siti Munira; Kamal, Siti Nur Elida Aqmar Mohd; Abu Bakar, Suriani; Osman, Nafisah; Jaafar, Juhana; Rahman, Mukhlis A; Ismail, Ahmad Fauzi
Summary: Solid oxide fuel cell (SOFC) performance depends greatly on the anode conductivity, which in traditional nickel‐yttria stabilized zirconia (Ni‐YSZ) anode is determined by the Ni content that is infamous for its coking problem under hydrocarbon fuel. Without the use of high content of Ni, anode conductivity can be elevated by adding an external metal layer on top of the anode. In this study, we present the incorporation of copper (Cu) metal layer on top of the anode of micro‐tubular SOFC by applying a modified sol‐gel method using syringe deposition technique at various chemical compositions and deposition cycles. Cu sol was found best to be made up of 2:1:8 ratio of Cu: citric acid: ethylene glycol, with 1.36 μm metal layer formed at 5 deposition cycle, and no obvious increase in thickness after the fifth cycle. The Cu layer elevated the conductivity by 10 10 times compared to the uncoated anode. However, the coated layer also reduced the gas permeability by 10 times in the anode, which resulted from the blocking of a nano‐sized pore in the anode, rather than the micron size pore. This blocking can be resolved by increasing the amount of micron‐sized pore by using pore former during anode fabrication. From electrochemical impedance spectroscopy (EIS), Cu coating reduced the ohmic resistance ( R ohm ) and charge transfer resistance ( R ct ). From the current‐voltage curve, the maximum power density (MPD) was found to increase linearly with the increase of the Cu coating cycle, but the value is almost stagnant at 2.3 to 2.5 mW cm −2 when the coating cycle of more than 4 was employed. This suggests that anode gas permeation plays an important role in anode conductivity. The findings from this study suggested that 5 deposition cycle shows to be the optimal coating layer required to achieve the percolation threshold without unnecessary loss in permeability. Abstract : This study aims at elevating the anode conductivity of ceria‐zirconia based anode of micro‐tubular solid oxide fuel cell by fabricating metallic copper layer on top of the anode using modified sol‐gel method. The copper layer elevated the conductivity by 10 10 times, reduced ohmic and charge transfer resistance but also reduced the gas permeability by 10 times in the anode. This blocking can be resolved by increasing the amount of micron sized pore by using pore former during anode fabrication.